1, 2‐Phosphaborines: Hybrid Inorganic/Organic P–B Analogues of Benzene. (28th August 2015) - Barnard, Jonathan H.; Brown, Paul A.; Shuford, Kevin L.; Martin, Caleb D.
Abstract Photolysis of the cyclic phosphine oligomer [PPh]5 in the presence of pentaarylboroles leads to the formation of 1, 2‐phosphaborines by the formal insertion of a phenylphosphinidene fragment into the endocyclic CB bond. The solid‐state structure features a virtually planar central ring with bond lengths indicating significant delocalization. Appreciable ring current in the 1, 2‐phosphaborine core, detected in nuclear independent chemical shift (NICS) calculations, are consistent with aromatic character. These products are the first reported 1, 2‐BPC4 conjugated heterocycles and open a new avenue for BP as a valence isoelectronic substitute for CC in arene systems.